Brief review on the roles of neutrophils in cancer development. Issue 2 (24th September 2020) - Long, Wang; Chen, Jingjing; Gao, Chen; Lin, Zhi; Xie, Xubiao; Dai, Helong
Abstract: Neutrophils, which are traditionally regarded as a hallmark of inflammation, are also a member of the intratumoral immune cells. The roles of neutrophils in cancer development are diverse and undefined. So far, they are known to be involved in tumor initiation and tumor cell proliferation and metastasis. They show heterogeneity in both phenotypes and functions during early versus late stage of cancer development. Because they are also associated with the clinical outcomes of various types of solid tumors, cancer treatments that target neutrophils might be highly effective. In this review, we briefly cover the latest findings on the multiple roles of neutrophils in cancer development and point out the future directions as well. Graphical Abstract: Reviews how neutrophils support tumor growth, enhance tumor cell proliferation, escort circulating tumor cells for metastasis.